Enhanced Performance Analysis and Blade Profile Optimization of a Vertical Axis Wind Turbine Using CFD - Vikas Shende (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Small-scale vertical axis wind turbines (VAWTs) like the Savonius rotor are attractive for decentralized power generation due to their simple design, omni-directional wind acceptance, and good self-starting capability. However, conventional Savonius turbines suffer from low aerodynamic efficiency and performance, partly caused by flow separation and turbulence around the blades. This paper presents a performance analysis and blade profile optimization for a Savonius VAWT using computational fluid dynamics (CFD) simulations in ANSYS Fluent. An innovative blade design – incorporating a modified blade profile and end-plates – is proposed to enhance turbine output. The baseline configuration (with straight rectangular blades) and the optimized design were modeled in NX 6.0 and evaluated under identical conditions in Fluent 14.5. Transient CFD simulations at 10 m/s wind speed were performed to compare pressure distribution, flow velocities, turbulence characteristics and torque/momentum between the designs. The CFD results indicate that the optimized blade yields a higher pressure differential across the turbine and nearly double the flow velocity through the rotor (due to improved drag capture), relative to the baseline. Turbulent kinetic energy in the rotor wake is reduced with the new design, suggesting smoother flow with less energy dissipation. An experimental prototype of both the conventional and modified Savonius rotors was fabricated and tested outdoors to validate the CFD findings. Field tests showed that the modified blade profile with end-plates achieved higher rotational speeds and an 8–9% reduction in noise compared to the traditional rotor. Overall, the combination of CFD analysis and experimental results demonstrates that the optimized Savonius rotor design offers superior aerodynamic performance and quieter operation. This study contributes a viable approach to improving VAWT efficiency through blade profile optimization and provides insights for further development of high-performance, low-noise wind turbines for sustainable energy.